(untitled) (Eurasian Scientific Herald, 2023)
This article assesses the sociol-entrepreneurship environment, analyzes the key areas, identifies problems and opportunities, and sets strategic plans and about how it helps to determine the road for mastering entrepreneurship, and assessing the sociolentrepreneurship environment is very important for the development of Higher Education Institutions. This assessment will help Higher Education Institutions grow, innovate, collaborate with customers, and improve business performance